Systematic Evaluation of Reference Protein Normalization in Proteomic Experiments - Zauber, Henrik; Schüler, Vivian; Schulze, Waltraud X. (Frontiers in Plant Science, 2013)
Quantitative comparative analyses of protein abundances and their modifications have become a widely used technique in studying various biological questions. In the past years, several methods for quantitative proteomics were established using stable-isotope labeling and label-free approaches. We systematically evaluated the application of reference protein normalization (RPN) for proteomic experiments using a high mass accuracy LC-MS/MS platform. In RPN each peptide intensity is normalized to an average protein intensity of a spiked-in reference protein per sample. The main advantage of this method, compared to other label-free normalization strategies, is to avoid fraction of total based relative analysis of proteomic data, which is often very much dependent on sample complexity. We could show that reference protein ion intensity sums are reproducible enough to ensure reliable normalization. We validated the RPN strategy by analyzing changes in protein abundances induced by nutrient starvation in Arabidopsis. Beyond that, we provide a principle guideline for determining optimal combination of sample protein and reference protein load on individual LC-MS/MS systems.